2018
DOI: 10.30935/cet.414808
|View full text |Cite
|
Sign up to set email alerts
|

Results from a Study for Teaching Human Body Systems to Primary School Students Using Tablets

Abstract: The paper presents the results from a study which examined whether tablets together with a mobile application with augmented reality features can help students to better understand the functions of the respiratory and the circulatory system. The target group was 75 sixth-grade primary school students, divided into three groups. The first group was taught conventionally; students studied using a printed handbook. In the second, a constructivist teaching model was used, but the instruction was not technologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 40 publications
0
12
0
2
Order By: Relevance
“…How the educational effect the findings were represented in through suggestions (for teachers, schools, students, and future research) some of the studies that is not been related to the educational field were excluded including studies that have non-teacher and non-student study groups except the future research findings which are based on all studies. As it can be understood from Table 9, it shows that there are variables higher in the frequency which is three participation in in-service training program, including activities to increase motivation, including activities for increasing self-efficacy, and suggested for teachers to include in the teaching process to improve teaching and learning methods in our total 52 studies there is 31 studies that is directed toward the educational effect the most frequent suggestion was to include activate to increases motivation and including activities for increasing selfefficiency in those studies it was suggested that they will help the students in providing activities that will increase their efficiency and motivation with help from the schools administration in the studies like Fokides and Mastrokoukou (2018), the least suggestion category were ensuring trust in students some stated that the students today are familiar with the technology more than the past five years and the fact that it is easier to be used since everyone uses phones daily for the studies by Celik et al (2020) and Kul (2019) are example for the studies with the highest frequency suggestion was to include participation training program which is related to the teachers and students and schools, its suggested that teachers need to be informed about the technology and given a full information about the concept and the technology use in education applications in different area, with providing with porpita training until they become more comfortable in using the technology as source in education materials, the studies reached a common conclusion which is that Mobile Augmented Reality technology can enhance learning and teaching methods. As shown in Table 10, the students have fewer negative thoughts toward the use of the technology but unfortunately, the students do not show that much trust in using it during the exams or being part of their training process in schools only two studies the students were supporting it the variable with higher frequency was the raising self-efficiency with 17 studies and then comes the developing a positive attitude toward the use of the technology in a classroom, they do not create negative attitudes and prejudices against health education, on the contrary, to develop a positive attitude towards the lesson, to move away from their prejudices and in the form of believing that they can be successful in health education.…”
Section: The Effect Of Findings On Health Educationmentioning
confidence: 99%
“…How the educational effect the findings were represented in through suggestions (for teachers, schools, students, and future research) some of the studies that is not been related to the educational field were excluded including studies that have non-teacher and non-student study groups except the future research findings which are based on all studies. As it can be understood from Table 9, it shows that there are variables higher in the frequency which is three participation in in-service training program, including activities to increase motivation, including activities for increasing self-efficacy, and suggested for teachers to include in the teaching process to improve teaching and learning methods in our total 52 studies there is 31 studies that is directed toward the educational effect the most frequent suggestion was to include activate to increases motivation and including activities for increasing selfefficiency in those studies it was suggested that they will help the students in providing activities that will increase their efficiency and motivation with help from the schools administration in the studies like Fokides and Mastrokoukou (2018), the least suggestion category were ensuring trust in students some stated that the students today are familiar with the technology more than the past five years and the fact that it is easier to be used since everyone uses phones daily for the studies by Celik et al (2020) and Kul (2019) are example for the studies with the highest frequency suggestion was to include participation training program which is related to the teachers and students and schools, its suggested that teachers need to be informed about the technology and given a full information about the concept and the technology use in education applications in different area, with providing with porpita training until they become more comfortable in using the technology as source in education materials, the studies reached a common conclusion which is that Mobile Augmented Reality technology can enhance learning and teaching methods. As shown in Table 10, the students have fewer negative thoughts toward the use of the technology but unfortunately, the students do not show that much trust in using it during the exams or being part of their training process in schools only two studies the students were supporting it the variable with higher frequency was the raising self-efficiency with 17 studies and then comes the developing a positive attitude toward the use of the technology in a classroom, they do not create negative attitudes and prejudices against health education, on the contrary, to develop a positive attitude towards the lesson, to move away from their prejudices and in the form of believing that they can be successful in health education.…”
Section: The Effect Of Findings On Health Educationmentioning
confidence: 99%
“…One study specified the context of use (English courses) but not the activities performed (Shadiev et al 2017). Four studies assessed perceptions after the use of a specific app involving collaborative work (Fokides and Mastrokoukou 2018) or individual exercises and document consultation (Huang et al 2017;Hwang et al 2015;Lin 2014). One study involved several reading tasks (Kaman and Ertem 2018).…”
Section: Contexts Of Tablet Use and Perception Measuresmentioning
confidence: 99%
“…The collaborative aspects of tablets use were investigated by two studies. Fokides and Mastrokoukou (2018) showed that students liked using tablets in a collaborative way. Lin et al (2012) compared two modalities of collaborative use: some groups involved four students working together with only one tablet (1:m).…”
Section: Attitude and General Perception Factorsmentioning
confidence: 99%
“…Μάλιστα, λόγω των αδυναμιών τους, είναι σχεδόν βέβαιο ότι δυσκόλεψαν τους μαθητές στην κατανόηση του γνωστικού αντικειμένου κάτι που, με τη σειρά του, είχε αρνητικό αντίκτυπο στα γνωστικά αποτελέσματα. Η δυσκολία εύρεσης εμπορικών εφαρμογών με αξιόλογη παιδαγωγική αξία (Fokides & Mastrokoukou, 2018;Henderson & Yeow , 2012) και, ταυτόχρονα, οι δυσκολίες κατασκευής εφαρμογών από τους ίδιους τους εκπαιδευτικούς, οδηγούν, με μαθηματική ακρίβεια, στην αδυναμία αξιοποίησης του συγκεκριμένου τεχνολογικού εργαλείου στη διδασκαλία (Haβler et al, 2016). Υπάρχουν δύο πιθανές λύσεις σε αυτό το πρόβλημα.…”
Section: 18 122unclassified
“…Σημαντικό είναι ότι μάλλον δεν υπάρχει ένα καλά ανεπτυγμένο παιδαγωγικό πλαίσιο χρήσης των κινητών συσκευών (Prieto et al, 2014) και ότι απαιτείται συχνή επιμόρφωση των εκπαιδευτικών πάνω σε θέματα ενσωμάτωσης των tablets στη διδασκαλία (Haβler et al, 2016). Τέλος, ερευνητές τόνισαν την έλλειψη εμπορικών εφαρμογών με αξιόλογη παιδαγωγική/διδακτική αξία (Fokides & Mastrokoukou, 2018;Henderson & Yeow, 2012). Ως αντίβαρο, υπάρχει μία αυξανόμενη τάση να μελετώνται τα αποτελέσματα που μπορεί να έχουν εφαρμογές που έχουν κατασκευαστεί από τους ίδιους εκπαιδευτικούς (Bano et al, 2018).…”
unclassified